Morphology controlled synthesis of battery-type NiCo2O4 supported on nickel foam for high performance hybrid supercapacitors. (January 2021) - Phat, Doan Tien; Thao, Pham Manh; Van Nghia, Nguyen; Son, Luong Trung; Thu, Tran Viet; Lan, Ngo Thi; Quyen, Ngo Quy; Van Ky, Nguyen; Van Nguyen, To
Highlights: Morphology Controlled Synthesis of Battery-type NiCo2 O4 Supported on Nickel foam. High performance hybrid supercapacitor. The morphologies have a strong influence on the electrochemical properties of materials. The NNCO-1 sample delivers a superior specific capacity of 503.5 C g −1 at current density of 1 A g −1 . The synthesized materials maintained 95-97 % of the original specific capacity. Abstract: In this study, we successfully synthesized NiCo2 O4 supported on Ni foam (NNCOs) with different morphologies by changing the synthesis conditions. The research results of electrochemical properties show that the morphologies have a strong influence on the electrochemical properties of materials. Specifically, the nanosheet-like NNCO-1 sample exhibited an enhanced specific capacity of 503.5 C g −1 at current density of 1 A g −1, ca. 134-350 % higher than that of NNCO-2, NNCO-4 (nanorod-like) and NNCO-3 (grass-like). All materials also show high stability with the ability to maintain 95 to 97% capacitance after 2000 discharge cycles at a current density of 2 A g −1 . We hope that, the NNCO-1 material is promising electrode material for hybrid supercapacitor.